"Fighting Their Own Economic Battles": Saint Charles Lockett, Ethnic Enterprizes, and the Challenges of Black Capitalism in 1970s Milwaukee. Issue 1 (14th March 2016) - Moten, Crystal M.
Abstract : This article examines African American businesswoman Saint Charles Lockett, a self-proclaimed feminist and Ethnic Enterprizes, her company. Established in Milwaukee, Wisconsin in 1970 at the height of deindustrialization and Black Power, as well as the dawn of neoliberalism, Ethnic Enterprizes hired mothers who received welfare benefits. Its goal was to be a "gateway to gainful employment." After receiving numerous accolades, Lockett and Ethnic Enterprizes became mired in controversy because of its inability to pay its mother workforce more than the minimum wage. This led to its demise. Lockett and her firm deserve serious analysis because they provide an opportunity to examine a myriad of issues related to black working women, economic development, and the challenges of black capitalism in the urban industrial Midwest. Ethnic Enterprizes was Lockett's response to black women's exclusion from the industrial labor force, a route to black economic community development, and a vision for what could be possible for black working women. While examining the story of Saint Charles Lockett and Ethnic Enterprizes highlights the difficulties of excavating the voices of black working women who have been marginalized in the urban, industrial landscape, it also provides opportunities for theorizing about ways to magnify their voices in the historical record.